PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, NET PROFIT MARGIN DAN INFLASI TERHADAP HARGA SAHAM PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Pamungkas, Desi Wanti; Susilowati, Dw (Program Studi Ekonomi Pembangunan, 2023)
This study aims to determine how the effect of the Current Ratio, Debt to Equity Ratio, Net Profit Margin, and Inflation on stock prices both partially and simultaneously in property and real estate companies listed on the Indonesia Stock Exchange. The data in this study used secondary data using research data collection techniques in the form of documentation methods. The samples in this study were 20 property and real estate companies for the 2019-2021 period. The sampling technique in this study used a purposive sampling technique. The data analysis used in this research is panel data regression analysis with the help of the eviews-10 application. The results of testing the hypothesis show that partially or simultaneously the current ratio, debt to equity ratio, net profit margin and inflation have a significant positive effect on the stock prices of property and real estate companies listed on the Indonesia Stock Exchange in 2019-2021.